STEREOTYPES OF CHARACTERS IN CHILDREN’S STORIES ABOUT SCIENTIFIC ADVENTURES CREATED BY GenIA - Goldschmidt, Andréa Inês; Azevedo, Fernando José Fraga de (Literatura em Debate, 2025)
The proliferation of generative artificial intelligence (GenAI) means that we are witnessing a transformative change in education. While GenAI offers exciting possibilities for personalized learning and innovative teaching methodologies, its potential can end up reinforcing prejudices and perpetuating stereotypes, which raises ethical and pedagogical concerns regarding its use in the creation of stories aimed at children. This article aims to critically examine the use of GenIa in the production of children's literature, with regard to the promotion of stereotypes associated with characters who carry out scientific activities. Using an exploratory and qualitative methodology, we compared the narratives generated by four free applications available on the market. All the chatbots used followed the same prompts, and three were used. The stories were of the adventure genre, involving scientific activities related to insects. The analysis followed Content Analysis and the results show that AI is a powerful tool for promoting non-sexist narratives, capable of generating stories for children that challenge stereotypes and promote diverse gender representations. However, care must be taken, as not all chatbots were gender-equal and in some narratives there were still instances, albeit occasional, of reductionist stereotypes about scientists, which must be combated. The most important point was associated with the promotion of narratives involving children's characters, and valuing their contact with nature, in activities that involved investigations, collecting records and research, as well as the sharing of knowledge by the child researchers themselves.